Absorption cross section of canonical acoustic holes - Crispino, Luis C. B.; Oliveira, Ednilton S.; Matsas, George E. A. (Amer Physical Soc, 2007)
We compute numerically the absorption cross section of a canonical acoustic hole for sound waves with arbitrary frequencies. Our outputs are in full agreement with the expected low- and high-frequency limits.